Cross-border M&As and technological innovation: the moderating roles of formal and informal institutional distance. Issue 5 (26th August 2021) - Zhang, Hongxia; Yang, Huixin
Abstract : Purpose: To reconcile the existing contradictory conclusions on the relationship between cross-border mergers and acquisitions (M&As) and innovation, this paper aims to propose a theoretical model of the impact of cross-border M&As on technological innovation and explore the moderating role of institutional distance from the perspective of springboard theory and new institutional theory. Design/methodology/approach: Through the use of the two-way fixed effect model and the U-test method, the authors test the hypotheses based on a sample of cross-border M&A events of Chinese manufacturing enterprises during the period from 2006 to 2019. Findings: The research shows that there is an inverted U-shaped relationship between cross-border M&As and technological innovation. Furthermore, formal institutional distance moderates the inverted U-shaped relationship in such a way that it reaches its turning point at a smaller scale of cross-border M&As, and the inverted U-shaped relationship is steeper when formal institutional distance is relatively high. The informal institutional distance moderates the inverted U-shaped relationship in such a way that it reaches its turning point at a larger scale of cross-border M&As and the inverted U-shaped relationship is flatter when the informal institutional distance is relatively high. Originality/value: The research conclusions integrate heterogeneous views of the existing research, further clarify the influence mechanism and boundary conditions between cross-border M&As and technological innovation, identify the different moderating roles of formal institutional distance and informal institutional distance and enrich the literature on knowledge transfer and recombinant innovation during post-merger integration.